From conceptual model to conceptual framework: A sustainable business framework for community water supply businesses - Sukma, Narongsak; Leelasantitham, Adisorn (Frontiers in Environmental Science, 2022)
Businesses must do more than just safeguard their own financial interests if they are to survive in today's market. Sustainability, or long-term viability, requires consideration of society, the environment, and the global community. However, community-based businesses cannot use some of the current components of the sustainable business framework because they were created for large corporations. Both quantitative and qualitative approaches are used in this study. First, quantitative methods were used to develop a conceptual model for the organization's current needs by using the PPT, the TOE, and an Expectations Theory (ECT). A simple random sampling method was used to gather the data, with a sample size of 14 villages. Using a five-point Likert scale, the researcher gathered data from 2,584 households and collected 627 valid responses. After that, descriptive statistics were used to describe the data (frequency distributions, percentages, averages, medians, and standard deviations), and PLS-SEM was used to investigate the interactions between variables and launch the conceptual model using partial least squares (PLS) path modeling. First and foremost, qualitative by means of interactivity qualitative analysis (IQA). There are two ways to create a congested SID and an uncluttered SID: the Affinity Relationship Table (ART), the mapping of the Inter-Relationship Diagram (IRD), and the system influence diagram. According to the findings of the study, sustainable community water supply businesses are the primary driver. The conceptual framework presented in this paper is consistent with the results of the combination of quantitative and qualitative methods and the current constraints placed on community water supply businesses to thrive.